Moisture-resistant sustainable solar cell with RbGeI3 absorber layer - Raj, Manasvi; Aggarwal, Anshul; Kushwaha, Aditya; Goel, Neeraj (Journal of materials science, 2025)
RbGeI₃ was investigated as a moisture-resistant lead-free absorber for perovskite solar cells (PSCs), addressing stability and environmental concerns of lead-based materials. Strong ionic bonding in RbGeI₃ prevented moisture-induced phase transitions, ensuring long-term stability under varying humidity conditions. First-principles density functional theory (DFT) calculations optimized the PSC design, analysed band alignment, and evaluated RbGeI 3 ’s optical properties. The material showed a suitable band gap and strong light absorption, improving charge transport. DFT provided insights into the material’s electronic structure, charge carrier dynamics, and defect tolerance, enabling better material selection and optimization. A mathematical model for humidity analysis was developed to assess the impact of moisture on device stability. Poly(3-hexylthiophene-2,5-diyl) (P3HT), poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), and (2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene) (Spiro-OMeTAD) were used as hole transport layers (HTLs), while TiO₂ served as the electron transport layer (ETL), and fluoride-doped tin oxide (FTO) with Au acted as the back contact, ensuring efficient charge extraction. The optimized PSC achieved a power conversion efficiency (PCE) of 18.44%, fill factor (FF) of 74.19%, short-circuit current density (Jsc) of 30.84 mA/cm 2 , and open-circuit voltage (Voc) of 0.813 V, demonstrating high performance, moisture resistance, and potential for stable, cost-effective solar energy solutions. Graphical abstract This study presents an moisture resistant RbGeI 3 -based perovskite solar cell design, using RbGeI 3 as the absorber layer to address efficiency and stability challenges. By optimizing the ETL - TiO 2 and HTL – PEDOT: PSS, the device efficiency is enhanced. The figure below illustrates the optimised device structure and J-V characteristics, achieving a PCE of 18.44%, demonstrating its potential for highperformance, sustainable photovoltaic applications